Structure and Properties of Chemically-reduced Functionalized Graphene Oxide Platelets. Issue 5 (May 2015) - Pruna, A.; Pullini, D.; Busquets, D.
Abstract : Green reduction of graphene oxide (GO) functionalized with 3-aminopropyltriethoxysilane and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride/N-hydroxysuccinimide was performed by using ascorbic acid and sodium bisulfite. The obtained materials were characterized by thermo-gravimetric analysis, transmission electron microscopy, X-ray diffraction, UV‒Vis, Fourier transform infrared and Raman spectroscopy techniques. The results indicated a strong dependence of the materials properties such as deoxygenation degree, absorption peak shift, crystallite size and functionalization degree on the functionalization approach and reducing agent.